2009
DOI: 10.1002/int.20331
|View full text |Cite
|
Sign up to set email alerts
|

Sharing in teams of heterogeneous, collaborative learning agents

Abstract: This paper is focused on the effects of sharing knowledge and collaboration of multiple heterogeneous, intelligent agents (hardware or software) which work together to learn a task. As each agent employs a different machine learning technique, the system consists of multiple knowledge sources and their respective heterogeneous knowledge representations. Collaboration between agents involves sharing knowledge to both speed up team learning, as well as refine the team's overall performance and group behavior. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Research by Gifford & Arvin (2009) has shown that collaborative learning through heterogeneous groups can accelerate learning, as well as improve student performance and the entire group behaviors. The provision of complex problems can improve learning efficiency for each group member (Kirschner, Fred & Paul, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research by Gifford & Arvin (2009) has shown that collaborative learning through heterogeneous groups can accelerate learning, as well as improve student performance and the entire group behaviors. The provision of complex problems can improve learning efficiency for each group member (Kirschner, Fred & Paul, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The goal of evaluating these aspects through detailed team studies is to study whether teams are better than an individual, combining decisions from multiple learners is useful, and that heterogeneous learning algorithms leads to higher task performance/accuracy (Gifford and Agah, 2009). The following sections present experimental results and discuss general aspects of team learning and collaboration discovered as part of this research.…”
Section: Methodsmentioning
confidence: 99%
“…Many multiagent research efforts utilize the original discretized predator-prey pursuit environment shown in Figure 1, implementing a toroidal grid world and requiring the single prey to be blocked on all sides by four predators [7,21,22]. These studies tend to focus less on the structure of the environment and more on how specific sets of predator strategies impact cooperation and teamwork in homogenous and heterogeneous groups of predators.…”
Section: Modifications To the Predator-prey Pursuit Environmentmentioning
confidence: 99%